AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN ASET WAKAF PADA BAITUL MAL KOTA BANDA ACEH - yuliani, niki wili; Bustamam, Bustamam (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
This study has purpose to describe how accountability and transparancy in the management of waqf assets in baitul mal Banda Aceh . This study is descriptive qualitative study. Data is collected by interview to Baitul Mal Banda Aceh. The primary data collected by interview is used in this study. The results of this study indicate that generally, Baitul Mal Banda Aceh already has transparancy and accountability in its waqf assets management.